Engagement and disengagement with sustainable development : further conceptualization and evidence of validity for the Engagement/Disengagement in Sustainable Development Inventory (EDiSDI) - Moreira, Paulo (2022)
Correspondence concerning this article should be addressed to Prof. Paulo Moreira, Instituto de Psicologia e de Ciências da Educação, Universidade Lusíada, Rua de Moçambique 21 e 71, Porto 4100-348, Portugal. Email: paulomoreira@por.ulusiada.pt